By factoring I get x-3 divided by x+3
It is 2n^3 + 7n^2 - 13n + 3
b2 + ab - 2 - 2b2 + 2ab = -b2 + ab - 2 which cannot be simplified further.
Three minus three times six plus two is equal to -13.
(a - 2)(a^2 + 6)
X= plus or minus 1
Two plus 3 minus 2 times 1 squared plus 4 times 16 squared minus 4 times 2 is equal to 1,019.
Ti has plus three. Fe has plus three. O has minus two
it is 2y squared + 3y
Factor out -2: -2(x squared +11x-20). This is fully factored.
3 + -2 = 1
It is a quadratic equation in X, with two real roots.
Let square = [x] -4+3*(-2)*[-4]+[3x-2x]=-4-6-2+[x]=-12+[x]The answer is negative 12 plus squared x.
Three Times A Number x Minus Two translates to 3x-2 Three Times A Number x Minus Two translates to 3•x-2 Three Times A Number y Minus Two translates to 3y-2 Three Times A Number z Minus Two translates to 3z-2